Play of the Subconscious: on the Saṃskāras and Vāsanās in Classical Yoga Psychology - Beinorius, Audrius (Acta Orientalia Vilnensia, 2004)
The present study attempts to deepen the existing scholarly understanding of the various conceptual issues related to the problem of unconscious in Indian philosophy. An attempt is made to determine and classify the semantic content of a selected number of psychological concepts, notably saṃskãras and vāsanās, as it is found in the philosophical and religious texts of Patañjali’s Yoga sūtra and the basic commentarial literature thereon. Seven main features, or functions, of these concepts in Yoga tradition are distinguished. Finally, some significant differences between Yoga psychology and Western psycho-analysis regarding the understanding of the nature of the subconscious are mentioned. The most important point of similarity is that according to both Yoga and psychoanalysis the subconscious is regarded as the determining factor in conscious life. Belonging to the core of the Indian psychological system, the conception of saṃskãras and vāsanās in a way foreshadows the modem notion of the subconscious / unconscious / preconscious.